Fundamentals of Entrepreneurship (ENT300) : Sea ocean diving & marine services sdn bhd (services) / Debbra Juman … [et al.] - Juman, Debbra; Hannah, Hazel; Tricia, Laura; Alfred, Ordellia; Bujang, Preslyvia (2018)
Sea ocean Diving Marine & Services Sdn Bhd is an established company since April 2015. The company is managed by the professional workforce with vast experience in the capacity of Diving, ROV and Marine operations. Seaocean Diving Marine & Services Sdn Bhd provide inshore and offshore diving industry with expert personnel and certified equipment. The mission for this company is 'we take pride in our work”. They strive for to provide their clients with integrity and professionalism. The problems that the company faced are recognition, limited professional personnel, working hours and favoritism.